Chromatographic Characterization and Method Development for Determination of Levetiracetam in Saliva: Application to Correlation with Plasma Levels - Imad I. Hamdan; Mervat Alsous; Amira Taher Masri (Journal of Analytical Methods in Chemistry)
Levetiracetam (LVT) is a widely used antiepileptic drug (AED). A less invasive sampling method for therapeutic drug monitoring (TDM) would be very useful particularly for children. Saliva has been shown as an adequate sample for TDM of some AEDs. Due to the high hydrophilicity of LVT its separation on common stationary phases is quite a challenge so that previous methods for determination of LVT in saliva employed either gradient high performance liquid chromatographic (HPLC) system or mass spectrometer as a detector. In this study the retention behavior of LVT on some common stationary phases was examined, with C8 being the most retentive. A simple isocratic HPLC method that is based on simple protein precipitation was developed and validated for the determination of LVT in saliva. The method was applied to a sample group of epileptic children for the purpose of assessing potential correlation with plasma LVT levels and to investigate patient’s compliance. The results confirmed a reasonable correlation between plasma and salivary levels of LVT (R = 0.9) which supports the use of saliva for TDM of LVT. The study also revealed a significant percentage of epileptic patients having LVT levels below the estimated therapeutic range.